Diseases of the nervous system among schoolchildren and youth in modern training conditions - Fedorchenko, R. A.; Mykhaylenko, V. L.; Taranov, V. V.; Badiuk, N. S. (Journal of Education, Health and Sport, 2017)
The health of children and youth is an integral indicator of the well-being of society and an indicator of social and environmental problems. The aim of the study is to study the prevalence of mental illnesses and disorders of the nervous system in children, adolescents and youth in anthropogenic pressure; аssessment of personal health of adolescents and young people based on the results of the questionnaire according to the WHOQOL-BREF standard. To implement the goals and objectives, bibliographic, comparative, and statistical methods were used. In children and adolescents, there is an increase in the prevalence of diseases of the nervous system and mental disorders by 7,5% and 4,5%, respectively. The incidence of mental disorders was highest in children under 6 years of age, and prevalence rates in school-age children. The maximum incidence of nerve diseases was also observed in children under 6 years of age. At school age, especially from 14 to 17-18 years, under the influence of external factors and "school risks", "psychoemotional instability" can arise. The indicator of "satisfaction" with the quality of life among young people is stable and high, which indicates the formation of a stable population of the population in the age range of 17-30 years, which is adapted to living and learning conditions.